(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The most up-to-date information on new businesses, products, services, commercials, offers, or promotions can now be found mostly on social media platforMs. Purchasing decisions are likely to be influenced by how consumers feel about a company’s products and image. Marketing is exceptionally crucial for the survival and growth of your business; it is important to choose the right social media platforms as a marketing tool that links customers with online retailers. The most popular social media platforms have made it simple for companies to connect with and engage with their potential customers. This research examines the Effects of social media on selected fast food chains: basis for marketing improvement. The demographic profile of the respondents was mostly 18-24 years old, with the highest number of male respondents, and most of the respondents were single. There are factors that need to be considered for improving social media marketing, especially in fast food chains. In terms of whether it helps increase the sales of fast-food chains, respondents agree that social media marketing can widen the audience range and is the most effective way to gain more sales. Surveys in social media engage customer interaction that leads to great bonds and loyalty from customers. Social media marketing will lead to customer satisfaction. The staff of fast food should know how effective social media marketing is. Fast food restaurants must pay more attention to social media marketing because it engages the company and also increases sales. Fast food companies must use social media marketing because it creates good relationships and builds trust in their customers. The staff of the fast- food company must cooperate with their marketing strategies. The future researchers and staff of the company must know how important social media marketing is in any aspect because it really helps the company a lot.